On the allocation of credit and aggregate fluctuations - Gomes, O. (2015)
Recent literature on financial development and growth has highlighted the possibility of endogenous business cycles arising for particular levels of a given credit multiplier. These studies concentrate on loans directed to the productive activity and neglect the role of credit to consumption. In this paper, we consider an endogenous growth model, where a representative agent must choose how to allocate credit; basically, the agent considers a simple rule where the share of credit to consumption reacts to deviations of the consumption - wealth ratio relatively to the corresponding steady state level. The setup generates nonlinear dynamics, which are analyzed both locally and globally.